Thinking and Action: A Cognitive Perspective on Self-Regulation during Endurance Performance - Brick, Noel E.; MacIntyre, Tadhg E.; Campbell, Mark J. (Frontiers in Physiology, 2016)
Self-regulation reflects an individual’s efforts to bring behavior and thinking into line with often consciously desired goals. During endurance activity, self-regulation requires an athlete to balance their speed or power output appropriately to achieve an optimal level of performance. Considering that both behavior and thinking are core elements of self-regulation, this article provides a cognitive perspective on the processes required for effective pace-regulation during endurance performance. We also integrate this viewpoint with physiological and performance outcomes during activity. As such, evidence is presented to suggest that what an athlete thinks about has an important influence on effort perceptions, physiological outcomes, and, consequently, endurance performance. This article also provides an account of how an athlete might control their cognition and focus attention during an endurance event. We propose that effective cognitive control during performance requires both proactive, goal-driven processes and reactive, stimulus-driven processes. In addition, the role of metacognition – or thinking about thinking – in pace-regulation will also be considered. Metacognition is an essential component of self-regulation and its primary functions are to monitor and control the thoughts and actions required for task completion. To illustrate these processes in action, a metacognitive framework of attentional focus and cognitive control is applied to an endurance performance setting: specifically, Bradley Wiggins’ successful 2015 Hour record attempt in cycling. Finally, future perspectives will consider the potentially deleterious effects of the sustained cognitive effort and self-control required during prolonged and strenuous endurance tasks.